2013
DOI: 10.1159/000355718
|View full text |Cite
|
Sign up to set email alerts
|

Central Obesity, C-Reactive Protein and Chronic Kidney Disease: A Community-Based Cross-Sectional Study in Southern China

Abstract: Objective: Previous studies have shown that central obesity is associated with chronic kidney disease (CKD). We hypothesized that the association of central obesity with CKD is modified by the presence of inflammation. To test this hypothesis, we performed this study. Methods: This was a cross-sectional study in southern China. Waist-to-height ratio (WHtR) was used as a central obesity index and C-reactive protein (CRP) was used as an index for inflammation. CKD was defined as estimated glomerular filtration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
2
28
1
Order By: Relevance
“…The results indicate that inflammation could have an important role in obesity-related adverse events. Our previous study also supported such a view [25].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results indicate that inflammation could have an important role in obesity-related adverse events. Our previous study also supported such a view [25].…”
Section: Discussionsupporting
confidence: 82%
“…However, our present study did not include inflammatory markers in the definition of metabolically healthy. Inflammation might be a potentially adverse downstream consequence of increased fat mass, and might also be part of the causal pathway between obesity and CKD [1,25]. Our previous study indicated that obesity is associated with inflammation and that inflammation modifies the links between obesity and CKD [25].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The metabolic disorders that occur in IR are involved in the pathogenesis of type 2 diabetes mellitus (type 2 DM), and when associated with dyslipidaemia, obesity and hypertension (AH), these conditions constitute metabolic syndrome (MS) 3. MS is characterized by a complex network of nutritional and metabolic disorders, including inflammation, oxidative stress, vitamin D deficiency, anaemia and high levels of C reactive protein (CRP) 3,4.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, controversies still remain regarding the relationship between decreased estimated glomerular filtration rate (eGFR560 mL/min/1.73 2 ) and individual factors in MetS. Some researchers reported that obesity indicated by elevated body mass index (BMI) which can induce renal injury 13 is an independent culprit in CKD, 14,15 while others observed a U-shaped association between weight change categories and development of CKD. 16 In addition, few studies have focused on the relationship of CKD with different levels of individual factors in MetS.…”
Section: Introductionmentioning
confidence: 99%